Statistical Anxiety as a Moderating Factor in the Relationship Between Academic Self-Efficacy and Motivational Orientations among Graduate Students - Zakri, Ali Mohammed Abdullah (European Journal of Social Science Education and Research, 2026)
This study investigates the moderating effect of statistical anxiety on the relationship between academic self-efficacy and motivational orientations among graduate students at Jazan University. A cross-sectional survey was conducted with 202 graduate students (91 males; 111 females) enrolled in statistics-intensive courses. Participants completed validated self-report measures of academic self-efficacy, motivational orientations, and statistical anxiety. Moderated multiple regression analyses were performed using Hayes’ PROCESS macro (Model 1), and simple slope analyses were conducted to evaluate conditional effects across low, medium, and high levels of statistical anxiety. Results indicate that academic self-efficacy is positively associated with motivational orientations. Statistical anxiety significantly moderates this relationship, attenuating the positive effect of self-efficacy on motivation at higher anxiety levels. Simple slopes analysis reveals that the association between self-efficacy and motivation is strongest at low statistical anxiety and progressively weaker at medium and high levels of anxiety. Statistical anxiety diminishes the extent to which graduate students’ academic self-efficacy translates into goal-directed motivational engagement. These findings suggest that interventions targeting anxiety management may enhance the effectiveness of self-efficacy in promoting motivation and academic engagement.
Keywords: Affective barriers; Anxiety; Efficacy, Higher education; Motivation.